Lebanese banks’ state of readiness to lift banking secrecy - Y. HAMDAR, Ghinda (Proche-Orient Études en management, 2018)
This paper aims to explore the level of readiness of Lebanese banks to adapt to a change highlighted by the international financial wave of transparency that oppresses banking secrecy worldwide.